2015
DOI: 10.1038/npp.2015.134
|View full text |Cite|
|
Sign up to set email alerts
|

Functional Uncoupling NMDAR NR2A Subunit from PSD-95 in the Prefrontal Cortex: Effects on Behavioral Dysfunction and Parvalbumin Loss after Early-Life Stress

Abstract: Exposure to early-life stress increases vulnerability to psychiatric disorders, including depression, schizophrenia, and anxiety. Growing evidence implicates aberrant development of the prefrontal cortex (PFC) in the effects of early-life stress, which often emerge in adolescence or young adulthood. Specifically, early-life stress in the form of maternal separation (MS) in rodents has been shown to decrease parvalbumin (PVB)-positive interneurons in the adolescent PFC; however, the mechanism underpinning behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 50 publications
4
34
0
Order By: Relevance
“…With regards to behavior, ELS-exposed subjects were more active than control subjects upon introduction to the open field arena, which may reflect a higher response to novelty that we have previously reported (Ganguly et al, 2015). Surprisingly, while ELS has been repeatedly shown to increase anxiety-like behaviors (Koe et al, 2016), here we observed that even after correcting for increased general locomotion, females exposed to ELS visited the center of the open field more often than control subjects—typically a measure of lower anxiety.…”
Section: Discussionmentioning
confidence: 49%
“…With regards to behavior, ELS-exposed subjects were more active than control subjects upon introduction to the open field arena, which may reflect a higher response to novelty that we have previously reported (Ganguly et al, 2015). Surprisingly, while ELS has been repeatedly shown to increase anxiety-like behaviors (Koe et al, 2016), here we observed that even after correcting for increased general locomotion, females exposed to ELS visited the center of the open field more often than control subjects—typically a measure of lower anxiety.…”
Section: Discussionmentioning
confidence: 49%
“…Furthermore, Npas4 deficiency has not been associated with increased anxiety‐like behavior in past studies using male mice, while PNS has been shown to induce anxiety‐like behavior in both sexes in adulthood . The PFC is a known contributor to the regulation of anxiety and environmentally induced loss of prefrontal PV during development has been associated with increased anxiety‐like behaviors (ie, References ). Thus the reduced number of PV‐expressing cells in the PFC of HET mice, when associated with other PNS‐induced dysregulation (eg, increased corticotrophin‐releasing hormone (CRH) in the amygdala) could contribute to the reduced time spent in the center of the open‐field observed in PNS HET mice.…”
Section: Discussionmentioning
confidence: 99%
“…During gestation, excessive maternal stress or glucocorticoid treatment causes adult offspring to exhibit increased anxiety-like and depression-like behaviors, as well as impaired learning [ 101 ]. Adolescent rats that received maternal separation stress as young pups have excess anxiety and overexpress NR2A, a NMDAR subunit [ 102 ]. Adult mice that were deprived of bedding early in life show increased aggression and impaired social recognition [ 103 ].…”
Section: Effects Of Stress On Cognition Memory and Moodmentioning
confidence: 99%